STRATEGI RUMAH SAKIT DALAM MENGHADAPI PERLUASAN TANGGUNG JAWAB HUKUM: KAJIAN LITERATUR - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
The expansion of legal responsibilities in the healthcare sector poses a challenge for hospitals to maintain professional and operational accountability. This study examines key strategies that hospitals can implement to address these challenges. The approaches discussed include strengthening internal policies, staff training and education, and the application of information technology to support legal compliance. With clear policies, continuously improved healthcare staff competencies, and integrated digital systems, hospitals can create a proactive work environment for managing legal risks. This study emphasizes the importance of holistic strategies to ensure quality of service while protecting the institution from potential legal litigation in the modern era.